Conference report 1st German - Chinese Symposium "functional and healthy food ingredients generated through state-of-the-art biotechnology" – Outcome & perspectives. (July 2019) - Stressler, Timo; Fischer, Lutz; Zhang, Yanyan; Huber, Irene; Jiang, Bo; Mu, Wanmeng; Nie, Shaoping
Abstract: In the light of growing populations, longer life expectancies, the current obesity epidemic, as well as consumer demands for safe and healthy food, there is an ever-growing responsibility for food scientists worldwide to come up with adequate solutions. Cooperation between China and Germany in this research area has developed steadily and successfully for many years and focuses on topics highly relevant for both countries, i.e. nutritional needs of an aging population, food authenticity and safety, and special diets when suffering from malnutrition, adverse food effects, or other food-related health impairments. Functional food ingredients and customized formulations can be instrumental to ensure a balanced and healthy nutrition; especially, if food design and processing takes into account how the food is metabolized. Indeed, the microbiome plays a vital role in that process and therefore was addressed in several presentations during the first German-Chinese Symposium on "Functional and healthy food ingredients generated through state-of-the-art biotechnology", which took place from September 12–14, 2018 at University of Hohenheim in Stuttgart. More than 35 speakers from 10 German and 5 Chinese Universities shared their current research results, discussed knowledge gaps and challenges related to the topic. This report summarizes the presentations given, highlights the main outcomes of the discussion and concludes with an outlook for further joint research. Highlights: State of the art and current trends in food production are summarized and discussed. Understanding individual food metabolization is key to a healthy nutrition. Analytical methods and tools need to be keep pace with novel food technologies. Research gaps were identified and will be addressed in collaborative projects.